Considering the Polemics of between Tasawuf and Fiqh: Analysis of the Thoughts of Sheikh Abu Nasr Al-Sarraj Al-Thusi in Kitab Al-Luma' - Hosen, Hosen; Mukit, Abdul; Kamiluddin, Kamiluddin (Proceedings of Annual Conference for Muslim Scholars, 2022)
One of the problems that occur in Islamic civilization is the existence of conflicts and debates between fellow Muslims. In the process of developing the religion of Islam, people should first examine the various controversies that have occurred throughout Islamic civilization. One of the controversies that occur among the Muslims is the controversy between the Sufis and the mutafaqqih regarding fiqh. This is due to differences in perception between the Sufis whose views are spiritual and the mutafaqqih who are outward in nature. In analyzing the data of this study, the author uses two theories, the theory of A.J. Arberry and the second is following the theory of Annemarie Schimmel. This study concludes that the opinion of Sheikh Abu Nasr Sarraj regarding the controversy of the Sufis against the mutafaqqih regarding fiqh and religion is so partial to justifying the Sufis. Because Al-Luma' was written by him as an arbiter of the conflict between the Sufis and the mutafaqqih in the past few centuries, especially about the untrue accusations made by the mutafaqqih. So, Sheikh Abu Nasr AL-SARRAJ has tried to mediate the conflict between the two groups through the book Al-Luma'